Semantics and Pragmatics in Jacinda Ardern’s Speech - Jaja Fatmaja; Gustaman Saragih (Deiksis, 2021)
The objective of this research is to find out: semantic (denotation and connotation), pragmatic (illocutionary act: assertive/representative, directive, commisive, expressive, and declarative), and frequency of occurrence of the semantic and pragmatic aspects. The research object of this study is utterances containing semantic and pragmatic aspects. The data were collected from Jacinda Ardern’s speech on Tuesday, 19 March 2019. The speech was delivered in front of the Parliament after the Christchurch mosque terror attack. The technique used is the noting technique, separating technique, and transferring technique in collecting the data. This research is aimed to analyze the semantic and pragmatic aspects of Jacinda Ardern’s speech. The method used in this research is the qualitative descriptive method that aims to analyze the semantic and pragmatic aspects of Jacinda Ardern’s speech. The research findings as follows: the writer focuses on two aspects of semantic, namely denotation and connotation, and in pragmatic aspects, the writer focuses on the illocutionary act, which is assertive/representative, directive, commisive, expressive, and declarative.  After the writer analyzed the data, the result is 1. Semantic aspects: a. denotation (76%), b. connotation (24%). The bigger presentations are denotation because each sentence mostly has literal or primary meaning. 2. Pragmatic aspects (illocutionary): a. assertive (46%), b. directive (12%), c. commisive (17%), d. expressive (8%) and e. declarative (17%). The bigger presentations are assertive speech acts because the speaker is representing reality.